CHARACTER AI IN EFL CLASSROOMS: STUDENT PERCEPTIONS AND EXPERIENCES - Irwanda Kusuma Ningsih; Farikah; Boris Ramadhika (Language and Educational Journal, 2024)
This study investigated the perceptions and experiences of EFL students using Character AI in their English learning process. Character AI, an advanced chatbot service designed for human-like interactions, offers potential benefits in language education. A qualitative approach was employed, involving 15 junior high school students at SMP Negeri 3 Magelang who interacted with Character AI for a 40-minute session. Data were collected through report cards and classroom observations and analyzed using thematic analysis. Findings indicate that students found Character AI engaging and enjoyable, enhancing their motivation and participation in learning English. The AI provided personalized feedback and realtime corrections, contributing to noticeable improvements in students' grammar and sentence construction skills. This study highlights the potential of Character AI as a valuable educational tool in EFL classrooms, emphasizing its role in enhancing student engagement, motivation, and participation while offering personalized feedback and real-time corrections